2015
DOI: 10.1007/s10072-015-2303-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and cognitive implications of cerebrospinal fluid oligoclonal bands in multiple sclerosis patients

Abstract: The presence of cerebrospinal fluid oligoclonal bands (CSF-OCB) in Caucasian patients with multiple sclerosis (MS) is supportive of diagnosis, though the relation with patients' clinical and specifically cognitive features has never been established or thoroughly examined. Thus, we investigated the clinical and for the first time the cognitive profile of MS patients in relation to CSF-OCB. We studied 108 patients with and without OCB and recorded demographic characteristics and detailed clinical data. A compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
(79 reference statements)
1
9
0
1
Order By: Relevance
“…The variation in seroprevalence of CSF-OCB could be related to different study designs and studied population 19 . In clinical aspects, OCB-positive and OCB-negative groups were similar, which is in line with most previous studies 20 .…”
Section: Discussionsupporting
confidence: 92%
“…The variation in seroprevalence of CSF-OCB could be related to different study designs and studied population 19 . In clinical aspects, OCB-positive and OCB-negative groups were similar, which is in line with most previous studies 20 .…”
Section: Discussionsupporting
confidence: 92%
“…Persistent intrathecal inflammation, demonstrated by the presence of OCBs in the CSF (25), is one of the hallmarks of MS in up to 95% of patients (25,26). Previous research demonstrated that the presence of CSF-OCBs in patients with MS tends to be related to widespread cognitive changes, especially worse visual memory (27) and larger periventricular lesion area on MRI (28). However, data on the relationship between inflammatory markers, such as CSF-OCBs or elevated IgG indices, and neurodegenerative markers, such as brain atrophy markers or RNFL thickness, in MS are limited (27).…”
Section: Introductionmentioning
confidence: 99%
“…Electrophoretically homogeneous IgGs were obtained using first affinity chromatography of the serum and CSF proteins on protein G-Sepharose and then by FPLC gel filtration as in [17][18][19]. The content of IgGs in serum and CSF of different patients as well as their concentration after their purification was estimated by standard immunochemical nephelometry according to [7][8][9]33,34].…”
Section: Purification Of Iggsmentioning
confidence: 99%
“…The isofocusing profiles DNase, MBP-, and histone-hydrolyzing activities of IgGs may be very different for various individuals, but the total IgG subfractions with all their activities are distributed from pH 3 to 10. and bacteria, at first there is an accumulation of antibodies against their components, which may have structural similarities with the components of blood and human cells [3,4]. Then, due to the mimicry of certain proteins of viruses and bacteria with those of humans, epitope spreading and bystander activation, a failure of the immune system can occur leading to the generation of Abs against its own components of the human body and, as a result, to the development of MS.One of the features of MS is the appearance of oligoclonal IgGs in the bone marrow CSF, revealing themselves as oligoclonal bands (OCBs) after CSF proteins isofocusing [5][6][7]. Nevertheless, OCBs were found in the CSF of patients with MS who were sick and non-sick with various bacterial and viral diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation